Effects of uses and gratifications on social media use: The Facebook case with multiple mediator analysis - Md. Alamgir Hossain (PSU Research Review, 2019)
Purpose – Billions of people around the world are experiencing new ways of interacting with people using the social networking sites (SNS). With the heavy traffic and technological capabilities, SNS offers remarkable gratifications to its users, but there is a lack of knowledge about how gratifications play a role in usage intention and whether there are other factors that influence this relationship. Therefore, this study aims to fulfill these research gaps. Design/methodology/approach – To explore these issues in depth, this study conceptualizes a comprehensive framework based on the theory of uses and gratification (UGT), habit and the subjective norm. Structural equation model is used to analyze the survey data. Findings – The results of the study reveal that UGT has a significant direct effect on usage intention. Furthermore, user habit and subjective norm play an important mediating role in the relationship between UGT and usage intention. Originality/value – The proposed framework would extensively contribute to the SNS literature and managerial insights by integrating personal and social factors in determining the user acceptance of the media.